Compulsão alimentar em adultos: um estudo epidemiológico de base populacional em Pelotas-RS - França, Giovanny Vinícius Araújo de (2010)
Objective: To estimate the prevalence of episodes of Binge Eating (BE) and to assess potential associations with nutritional status, satisfaction with current body weight, selfrated health status (SRHS) and body weight. Method: A cross-sectional populationbased study was carried out in the city of Pelotas, southern Brazil, with a sample of 2,097 individuals aged 20-59 years. BE was assessed through a questionnaire and defined as binging one or more times over the last three months before the interview. Results: The prevalence of BE and recurrent BE was 7.9% and 2.7%, respectively. In the adjusted analysis, obesity, fair/poor SRHS and body dissatisfaction remained strongly associated with BE. Discussion: This study showed a high prevalence of BE among adults in Pelotas, and its higher among younger women, fat and those who desire to weigh less. The current results are informative, but longitudinal studies would be needed to demonstrate the causal relationship between these events.